Integration Method of Religious Character Values in Chemistry Learning - Agung Nugroho Catur Saputro; Nurfina Aznam; Crys Fajar Partana (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
Science and religion are closely related because they come from one source, namely God Almighty. Therefore, the concept of the integration of science and religion must be implemented in the form of integrating religious characters in the science learning process. This study aims to identify and inventory the learning methods used to integrate religious character values in chemistry learning. This research is conducted by reviewing the literature, both in books, journal articles and popular scientific writings, about methods of integrating religious character values in chemistry learning. The main data sources are from journal articles that discuss the integration of religious characters in chemistry learning. The journal articles that became the main data source were ten articles obtained from the Google Scholar website using the keyword